2019
DOI: 10.15252/embj.2019102201
|View full text |Cite
|
Sign up to set email alerts
|

PLK 4 deubiquitination by Spata2‐CYLD suppresses NEK7‐mediated NLRP3 inflammasome activation at the centrosome

Abstract: The innate immune sensor NLRP3 assembles an inflammasome complex with NEK7 and ASC to activate caspase-1 and drive the maturation of proinflammatory cytokines IL-1b and IL-18. NLRP3 inflammasome activity must be tightly controlled, as its overactivation is involved in the pathogenesis of inflammatory diseases. Here, we show that NLRP3 inflammasome activation is suppressed by a centrosomal protein Spata2. Spata2 deficiency enhances NLRP3 inflammasome activity both in the macrophages and in an animal model of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 49 publications
3
55
0
Order By: Relevance
“…Subsequently, the deubiquitinated Plk4 binds to and phosphorylates NEK7 at Ser204, which results in a weakening of the interaction between NEK7 and NLRP3. This process is necessary for NLRP3 inflammasome activation (102). Additionally, ubiquitin ligase was also recognized as an important partner in the modification of Plk4.…”
Section: Ubiquitylation and Deubiquitylation Of Plk4mentioning
confidence: 99%
“…Subsequently, the deubiquitinated Plk4 binds to and phosphorylates NEK7 at Ser204, which results in a weakening of the interaction between NEK7 and NLRP3. This process is necessary for NLRP3 inflammasome activation (102). Additionally, ubiquitin ligase was also recognized as an important partner in the modification of Plk4.…”
Section: Ubiquitylation and Deubiquitylation Of Plk4mentioning
confidence: 99%
“…However, a subsequent study found a novel complicated post-translation modification of NEK7. Specific centrosome-localized spata2 recruits CYLD for the deubiquitination of polo-like kinase 4 (PLK4), which further binds to and phosphorylates NEK7 at Ser204 ( Yang et al, 2019 ). Thereby, this phosphorylation modification of NEK7 suppressed its binding with NLRP3 and inhibited NLRP3 inflammasome activation ( Yang et al, 2019 ).…”
Section: Nek7 In the Regulation Of Nlrp3 Inflammasome Activationmentioning
confidence: 99%
“…Specific centrosome-localized spata2 recruits CYLD for the deubiquitination of polo-like kinase 4 (PLK4), which further binds to and phosphorylates NEK7 at Ser204 ( Yang et al, 2019 ). Thereby, this phosphorylation modification of NEK7 suppressed its binding with NLRP3 and inhibited NLRP3 inflammasome activation ( Yang et al, 2019 ). In addition, HDAC6-mediated MTOC localization of NLRP3 may ensure the engagement of centrosomal kinase NEK7 ( Magupalli et al, 2020 ).…”
Section: Nek7 In the Regulation Of Nlrp3 Inflammasome Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…3), with glutathione S‐transferase omega‐1 (GSTO1‐1) mediating deglutathionylation of NEK7 to promote NLRP3 activation 81 . NEK7 is also phosphorylated by polo‐like kinase 4 (PLK4) at Ser204 that attenuates NEK7‐NLRP3 interaction, therefore suppressing inflammasome activation 82 …”
Section: Nek7mentioning
confidence: 99%